Effects of changing exposure to neighbourhood greenness on general and mental health: A longitudinal study. (May 2015) - Weimann, Hanna; Rylander, Lars; Albin, Maria; Skärbäck, Erik; Grahn, Patrik; Östergren, Per-Olof; Björk, Jonas
Abstract: Green neighbourhood environments have been associated with physical and psychological wellbeing in adults. Access to greenness is potentially more important in vulnerable subgroups. In this study based on longitudinal survey data from southern Sweden the cohort was divided into prognostic groups for good self-reported general ( n =8891) and mental ( n =9444) health. We used independent survey data to assess perceived neighbourhood greenness in 1 km 2 areas, and estimated effects of changing exposure longitudinally stratified by prognostic group. The overall effect on health was small and statistically uncertain (for general health OR 1.04, 95% CI 0.98–1.10, for mental health OR 1.07, 95% CI 1.00–1.14). A more beneficial effect of increased greenness was indicated among subjects with lowest prognostic of good general health (OR 1.24, 95% CI 1.01–1.52). The study provided only weak evidence for beneficial effects of increased neighbourhood greenness triggered by changing residence. It seems that altered life circumstances, e.g. changed civil or socioeconomic status that often trigger a decision to move, are also the key determinants of the health consequences of changing residence. Highlights: The overall effect of changing greenness exposure on wellbeing was weak. More beneficial effects of increased greenness was indicated in a vulnerable subgroup. Subgroups that would benefit from increased greenness may lack abilities to move. Future studies should assess effects of improved greenness in less affluent areas.